Adaptive Reuse Gedung Arsip Bank Jateng di Kawasan Cagar Budaya Pekojan Semarang - Fitri Dwi Indarti; Rohman Eko Santoso; Retno Rizkia (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Bank Jateng Archive Building located on Jalan Pekojan No. 2 Semarang is the first building owned by Bank Jateng which was occupied as the second headquarters in 1969. In 1981 the Head Office of Bank Jateng moved to Jalan Pemuda No. 4A Semarang and currently the building is used as an Archive Building.Considering the age of the building, the condition of the building that has not been maintained for a long time and the rarely used of the building, the building must be used by filling it with new activities or activities that intend to revive the use of the building. Reviving or revitalizing abandoned buildings allows the existing building to be used for new purposes. By giving new life to abandoned buildings, especially those of high historical importance, it can be transformed into something beneficial to the surrounding environment, especially by incorporating modern functions that are in line with the times to invite the activities of users who need them. With a qualitative method, this research will analyze in detail the aspects that can be used to become an adaptive reuse building concept that has the goal of providing a new function into an abandoned building, providing a new design without destroying the entire existing building structure and elements in it. The concept applied to the adaptive reuse of the Bank Jateng Archive Building macroly maintains the spatial structure. It's just that in a certain space it is an adaptation related to the urgency of the building's function, applicable regulations, and building technical standards, which in this case emphasizes the value of the safety of the space function and the application of ergonomic and inclusive design. According to the identification that has been carried out on the Bank Jateng archive building, it is known that the building style is something that must be maintained. With the main elements forming the original façade will be maintained. And improve the aesthetic harmony of the façade.